Taxonomic update of the benthic marine red algae (Rhodophyta) from the Mexican Atlantic - García García, Annie May Ek; Cabrera Becerril, Ernesto; Núñez Reséndiz, María Luisa; Dreckmann, Kurt M.; Sentíes, Abel (Instituto de Ecología, A.C., 2020)
Background and Aims: Since the contributions of Dreckmann in 1998, and Ortega et al. in 2001, there are no other integrative studies for the Mexican Atlantic seaweeds in which modifications and taxonomic actualizations were considered for this regional phycological flora. Hence, our main objective was to present an update for the marine benthic red algae from the Mexican coast of the Gulf of Mexico, and the Mexican Caribbean Sea, in which all the new records are included for the region since the contributions mentioned above. Materials and Methods: The information about the species was obtained through the analysis of all the specialized literature published for the region since 2001, as well as some previous records not considered before, and a revision of the databases of the UAMIZ Metropolitan Herbarium. Synonymy and nomenclatural status, as well as the classification system used, were revised in AlgaeBase. Key results: A checklist composed of 451 species and 13 infraespecific categories of red algae was obtained; these where distributed in 4 classes, 23 orders, 52 families, and 171 genera. The currently accepted name, synonymy, and distribution are mentioned for each species. An asterisk indicates previous records (prior to 2002), as well as its distribution in different habitats. Conclusions: The present contribution revealed two main changes to the previously known flora of the red algae from the study area. The first one falls in the domain of nomenclature, and implies a modification in their classification (families, genera, and species). The second one has an effect on the number of species present. As a consequence, it is evident that constant floristic monitoring is required along the coasts of the Mexican Atlantic.